THE INFLUENCE OF EARLY LITERACY CHARACTERISTICS AND SES ON THE LITERACY ACHIEVEMENT OF STUDENTS WHO SPEAK NON-DOMINANT LANGUAGES IN INDONESIA - Kevin M Wong (IJIET (International Journal of Indonesian Education and Teaching), 2019)
Across the world, children from non-dominant language speaking families are not performing as well as their peers who speak a dominant language when they enter school. The current study examines the case of Indonesia, investigating the influence of language background status, early literacy characteristics, and socioeconomic status on literacy achievement in Indonesia. Drawing from the PIRLS 2011 dataset (N = 2,725), findings reveal that there is a significant association between each variable and literacy achievement, and that socioeconomic status explains literacy achievement most strongly among 4th grade students in Indonesia. Implications are discussed.DOI:doi.org/10.24071/ijiet.2019.030211